Kapitalisasi Modal dan Kepentingan Elit Politik (Studi Arena Perebutan Pemimpin Lokal Antara Anak Adat Moi di Kabupaten Sorong 2017) - wahid, bustamin; Refra, Mohamad Saleh; Basri, La (Jurnal Noken: Ilmu-Ilmu Sosial, 2021)
Political dynamics today is very competitive, all aspects are used as references in practical politics. For example, political elites refer to financial capital and social capital for political purposes (interest politics). The political elite in Sorong Regency makes the Moi custom as an access to legitimize sacredly for the sake of the election of local leaders. This article focused on assessing social capital and political elites in the election of local leaders, the scope of this study was in Sorong, and using social and elite capital theory as an analysis. Sorong regency is customary region of Moi tribe, custom becomes central and even big narration in election of local leader in Sorong regency. The hope and customary interests through the Moi customary council are able to fight for the rights and aspirations of Moi's indigenous peoples in determining their aspirations. To continue the aspiration of the community, the Moi custom council must make a decision through custom forum in Maladofok district of Sayosa to determine the readiness of customary man who deserve to be a leader in Sorong regency which in fact is the customary region of Moi. Â 